Recipient vessels for free flaps in advanced facial oncologic defects - Bruno Albuquerque Sousa; Fernando Luiz Dias; Marcus A. Acioly de Sousa; Marco Antônio Pinto; Jéssica Marquet Silva; Cláudio Roberto Cernea (Brazilian Journal of Otorhinolaryngology, 2023)
Objectives: To prospectively compare the results of microvascular flap reconstruction of midface and scalp advanced oncologic defects using superficial temporal versus cervical as recipient vessels. Methods: This is a parallel group clinical trial with 1:1 allocation ratio of patients who underwent midface and scalp oncologic reconstruction with free tissue flap from April 2018 to April 2022 in a tertiary oncologic center. Two groups were analyzed: those in whom superficial temporal vessels were used as the recipient vessels (Group A) and those in whom cervical vessels were used as the recipient vessels (Group B). Patient gender and age, cause and localization of the defect, flap choice for reconstruction, recipient vessels, intraoperative outcome, postoperative course, and complications were recorded and analyzed. A Fisher’s exact test was used to compare outcomes between the 2 groups. Results: On the basis of the different recipient vessels, 32 patients were randomized into 2 groups, and of these 27 patients completed the study: Group A with superficial temporal recipient vessels (n = 12) and Group B with cervical recipient vessels (n = 15). There were 18 male and 09 female patients with an average age of 53.92 ± 17.49 years. The overall flap survival rate was 88.89%. The overall complication rate for vascular anastomosis was 14.81%. The total flap loss rate in patients with superficial temporal recipient vessels was higher than the complication rate in those with cervical recipient vessels but with no statistical significance (16.67% vs. 6.66%, p = 0.569). Minor complications occurred in 05 patients without statistical significance between the groups (p = 0.342). Conclusion: In the group with superficial temporal recipient vessels, the postoperative rate of free flap complications was similar than the cervical recipient vessel group. Therefore the use of superficial temporal recipient vessels for midface and scalp oncologic reconstruction could be a reliable option.